β-frutofuranosidase de Cunninghamella echinulata PA3S12MM: purificação, caracterização bioquímica e aplicação na produção de açúcar invertido - Rasbold, Letícia Mara (2020)
In the most diverse industrial sectors, the use of enzymes has been increasingly required, replacing several conventional chemical processes. Although they are increasingly used, the high cost of commercial enzymes often ends up making essential steps more expensive, making it necessary to search for new enzyme sources. In this context, fungi stand out as promising microorganisms, since they are major producers of several enzymes with high added value. Among the enzymes produced by these organisms, there is β-fructofuranosidase (β-FFase), which catalyzes the hydrolysis of the α1↔2β glycosidic link in sucrose. This enzyme has applications in several industrial sectors, such as in the production of inverted sugar, equimolar mixture of glucose and fructose. Obtained from a process known as inversion, inverted sugar has greater sweetening properties than sucrose, as well as better solubility and greater resistance to crystallization and the growth of microorganisms, being used in the manufacture of cakes, breads, ice cream, jams and soft-centered candies. The production of inverted sugar through the enzyme β-FFase, although it originates a high quality product, presents considerable costs, being of fundamental importance the search for new sources and methodologies that make enzymatic catalysis feasible. Thus, the objectives of this work consisted of enzymatic screening, optimization, purification, characterization and application of Cunninghamella echinulata PA3S12MM β-FFase in inverted sugar production. From enzymatic screening assays, it was found that the fungus C. echinulata produces the enzymes polygalacturonase (20.8 and 16.06 U mL-1 ) and β-FFase (133.65 and 194.31 U mL-1 ) in extra and intracellular extracts, respectively. The highest production of β-FFase was verified in Vogel medium and the cultivation conditions were optimized through the central rotational compound design, where the maximum production of this enzyme was achieved when the fungus was cultivated for 8 days at 28 ° C and supplemented with 1% apple peel, reaching 1054.85 U mL-1 . The best conditions for pH and temperature of the enzyme present in the crude extract were pH 5.0 and 60 °C. The β-FFase was purified through ion exchange and molecular exclusion columns and presented a relative molecular mass of 89.2 kDa, maximum activity at pH 6.0 and temperature of 60 °C, in addition to presenting stability in alkaline pH and thermoactivation at 50 °C. It was found that the enzyme is multifunctional, since it hydrolyzed different substrates, and its activity increased in the presence of Mn2+ and DTT. The apparent values of Km, Vmax and Kcat for sucrose hydrolysis were 173.8 mmol L-1 , 908.7 mmol L-1 min-1 and 1388.79 s-1 , respectively. The carbohydrate content of the purified enzyme was 83.13% and the analysis of the hydrolysis and transfrutosylation products indicated that the enzyme was effective in the production of glucose and fructose, but did not show fructosyltransferase activity. The enzyme immobilized in calcium alginate showed good results in the conversion of sucrose, showing promise for industrial applications. The results suggest that C. echinulata PA3S12MM is an excellent producer of β-FFase, with high catalytic activity, stability in alkaline pHs, multifunctional character, in addition to showing promising results in the sucrose inversion.